Analysis of 330 kV B busbar tripping accident in a 330 kV substation. Issue 1 (1st December 2022) - Jiang, Fei; Zhang, Zhaoyu; Zhang, Suhui; Gao, Jian
Abstract: In this paper, the damage to the bus conductor and expansion joint caused by the tripping accident of bus B of a 330 kV line in Northwest China was taken as an example, and the reasons for the tripping accident were analyzed and improvement measures were proposed utilizing macro inspection and cross-cut test. The results showed that the main reason for this failure is that the manufacturer did not strictly implement the coating process, resulting in insufficient coating adhesion, and the coating gradually cracked and fell off during operation. The peeling coating caused air gap breakdown and ground flashover.